Targeting AML-associated FLT3 mutations with a type I kinase inhibitor - Jones, LaQuita M. (J Clin Invest, 2020)
Tyrosine kinase domain (TKD) mutations contribute to acquired resistance to FMS-like tyrosine kinase 3 (FLT3) inhibitors used to treat FLT3-mutant acute myeloid leukemia (AML). We report a cocrystal structure of FLT3 with a type I inhibitor, NCGC1481, that retained potent binding and activity against FLT3 TKD and gatekeeper mutations. Relative to the current generation of advanced FLT3 inhibitors, NCGC1481 exhibited superior antileukemic activity against the common, clinically relevant FLT3-mutant AML cells in vitro and in vivo.